Distal duodenal diverticulization. A resource in emergency surgery in the region of the Treitz angle - Ruso, Luis; Taruselli, Roberto (Cirugía del Uruguay, 2004)
The anatomic pecu/iarities and low incidence of patho/ogy in the region of duodeno-jejunal angle, render difficult arriving at a technica/ and tactic consensual criteria in urgency of this area. There fol/ows a brief initia/ experience of cases of wounds (2), and obstructive (1) and hremorrhagic (1) complications of tumors and diverticu/a, which were so/ved through a technique involving distal duodenal exc/usion and digestive transit restoration through a duodeno-jejunal anastomosis located between we/1-vascu/arized sectors removed from the patho/ogic area. The paper contains a review of other techniques and their limitations.